Japanese consumers’ valuation of rice and pork from domestic, U.S., and other origins - Peterson, Hikaru H.; Bernard, John C.; Fox, John A.; Peterson, Jeffrey M. (My University, 2014)
Adoption of country-of-origin-labeling (COOL) has important implications for U.S. food exports. We assess the impact of COOL on imported rice and pork for Japanese female consumers using an auction experiment. In a first round based only on taste, U.S., Japanese, and third country products were valued similarly. In a second round with information only on product origin, bids for domestic products increased while bids for U.S. and other foreign products declined. Allowing participants to taste products of known origin in a final round did not significantly change an approximate 40% valuation discount for products of U.S. origin.
Keywords: Country-of-origin labeling; Experimental auctions; Pork; Rice